ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hamdani; Isnawati (Universitas Lambung Mangkurat, 2015)
This study was conducted to analyze the effect of corporate governance mechanisms, (Ownership Concentration, Size of the Board of Commissioners, Board Size, Komisarin Independent Audit Committee, Debt Policy and Firm Size) on financial performance. This research was conducted on a manufacturing company in Indonesia Stock Exchange. The population in this study amounted to 148 companies manufacturing and samples were taken of 20 companies with a passing stage purposive sampling. The data used in this research is secondary data. Data taken from the companies listed in Indonesia Stock Exchange in 2010-2012 were obtained from the Indonesian Capital Market Director (ICMD). Data collection techniques using methods of documentation and analysis techniques using multiple linear regression model. Based on the results of hypothesis testing is known that the variable size of the board of directors, audit committee and manufacturing company size has no effect on CFROA on manufacturing companies in Indonesia Stock Exchange. Sementra independent commissioner terhdap CFROA significant negative effect on manufacturing companies in Indonesia Stock Exchange. Means that the more the number of independent komasaris sekamin lowering CFROA and vice versa. Variable concentration of ownership, board size and debt policies CFROA significant positive effect on the manufacturing company in Indonesia Stock Exchange